Consumers Willingness to Pay and Factors Affecting Organic Vegetable Purchasing Decisions - Sholvia Dwi Rahayuningsih; Anas Tain (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
Along with the development of modern society, it is increasingly aware of a healthy lifestyle. This is indicated by the increasing interest in organic products. The research objective was to determine the characteristics of consumers, the value of willingness to pay and the factors that influence the value of willingness to pay consumers to buy organic vegetables in Malang with the hope of helping CV. Kurnia Kitri Ayu Farm. This study uses nonprobability sampling with accidental sampling method. The data that has been collected is then analyzed quantitatively and qualitatively. Quantitative data were analyzed using the Contingent Valuation Method (CVM) and Factor Test. Qualitative data is presented in graphs and tables. The results showed that the value of willingness to pay (Willingness To Pay) for organic vegetables for kale was IDR 5,870 per 200 grams, for green spinach IDR 5,925 per 200 grams, for caisim commodity IDR 6,000 per 200 grams, while the TWTP value was IDR . 158,500 for kale, Rp. 160,000 for green spinach, and Rp. 162,000 for caisim. The factors that influence willingness to pay are lifestyle factors with an eigenvalue of 3.776, quality factors with an eigenvalue of 2.195, habit factors with an eigenvalue of 1.762, a reference factor with an eigenvalue of 1.184, and comfort and trust factors with an eigenvalue of 1.036.